Poverty in MENA : Advances and Challenges - Vishwanath, Tara (World Bank, Washington, DC, 2012)
On February 29, 2012, the World Bank released an updated dataset of internationally comparable poverty estimates. Poverty is assessed against two internationally comparable poverty lines: $1.25 and $2 a day per capita (measured using 2005 purchasing power parity exchange rates). The new global estimates indicate a significant reduction in the proportion of world population below the $1.25 per day per capita poverty line, from 43.1 percent to 22.4 percent between 1990 and 2008. On the other hand, the reduction in the number of poor people is less impressive, mainly on account of population growth during this period. As a result, the number of the poor in 2008 was still as high as 1.29 billion people, although it fell from 1.9 billion in 1990. Accuracy of estimates in the Middle East and North Africa (MENA) region will improve if data is collected more regularly by individual countries as well as shared more rapidly. On an encouraging note, in the recently released 2008 poverty numbers, three MENA countries and territories are included for the first time (namely, Iraq, Syria, and the West Bank and Gaza).